School construction strategies for universal primary education in Africa : should communities be empowered to build their schools? - Theunynck, Serge, 1947- (Africa Region human development series., 2008)
School Construction Strategies for Universal Primary Education in Africa' examines the scope of the infrastructure challenge in Sub-Saharan Africa and the constraints to scaling up at an affordable cost. It assesses the experiences of African countries with school planning, school facility designs, and construction techniques, procurement and implementation arrangements over the past thirty years. It reviews the roles of the various actors in the implementation process : central and deconcentrated administrations, local governments, agencies, social funds, NGOs, and local communities. Drawing.